Elements of a nurse-coordinated post-stroke home care rehabilitation in the Philippines: A cross-sectional study - Allan Paulo Blaquera; Gil P. Soriano; Hirokazu Ito; Yuko Yasuhara; Tetsuya Tanioka (Belitung Nursing Journal)
Background: Stroke is the leading cause of disability and the second leading cause of death worldwide. In the Philippines, there is a lack of a unified system for the care of community-dwelling patients with stroke. Furthermore, rehabilitation facilities are underutilized, and human resources and financial support policies are lacking. Nurses have become valuable human resources in rehabilitation. Current literature has inconsistent and weak evidence on the effectiveness of home-based post-stroke rehabilitation.